2023
DOI: 10.1111/bjso.12649
|View full text |Cite
|
Sign up to set email alerts
|

Integration, urban citizenship, and spatial aspects of (new) mobilities: Greek migrants' constructions of integration in European cities

Abstract: This study aims at casting light on the ways in which spatial aspects of mobility and belonging serve as social‐psychological discursive resources used by Intra‐European Greek immigrants in order to account for integration. For the purposes of the study, 17 virtual interviews with Greek migrants in European cities were analysed. Interview discussion was facilitated by photographs of participants' meaningful places. In the analysis, accounts of belonging to the community ‘in general’ were juxtaposed to accounts… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 96 publications
0
1
0
Order By: Relevance
“…It was inversely proportional to the size of the community and increased with homeownership, participation in community activities, length of residence in the municipality, and being born in or choosing it as a place to settle. In the urban context, it was found that foreign-born individuals, especially Africans and Latin Americans, expressed a lower sense of identity and belonging due to integration difficulties and limited participation in local culture-related activities, such as festivals and the local language ( 55 , 71 , 83 , 84 ).…”
Section: Discussionmentioning
confidence: 99%
“…It was inversely proportional to the size of the community and increased with homeownership, participation in community activities, length of residence in the municipality, and being born in or choosing it as a place to settle. In the urban context, it was found that foreign-born individuals, especially Africans and Latin Americans, expressed a lower sense of identity and belonging due to integration difficulties and limited participation in local culture-related activities, such as festivals and the local language ( 55 , 71 , 83 , 84 ).…”
Section: Discussionmentioning
confidence: 99%